CCL3 Promotes Germinal Center B Cells Sampling by Follicular Regulatory T Cells in Murine Lymph Nodes - Benet, Zachary L.; Marthi, Matangi; Ke, Fang; Wu, Rita; Turner, Jackson S.; Gabayre, Jahan B.; Ivanitskiy, Michael I.; Sethi, Sahil S.; Grigorova, Irina L. (Frontiers in Immunology, 2018)
Previous studies and our findings suggest upregulated expression of proinflammatory chemokines CCL3/4 in germinal center (GC) centrocytes. However, the role of CCL3/4 for centrocyte interactions with follicular T cells and regulation of humoral immunity is poorly understood. We found that CCL3 promotes chemotaxis of Tfr cells ex vivo. Two-photon imaging revealed that B cells-intrinsic production of CCL3 promotes their probing by follicular regulatory T cells (Tfr) within GCs of murine lymph nodes. Overall this study suggests that CCL3 facilitates direct interactions of foreign antigen-specific GC B cells and their negative regulation with Tfr cells in vivo.